THERMAL ANALYSIS AND OPTIMIZATION OF HIGH POWER LED ARMATURE - (:unkn) unknown (VINCA INST NUCLEAR SCI, 2017)
It is an effective way of energy conservation to use high power LED armature in street lighting. However, there exists some restrictions in front of the usage of that, like overheating of LED chips and high weight of armature case. Generally, aluminum heat sinks are attached to housing of the armature to get effective working of LED armature. In this study, a street type high power LED armature has been modeled numerically, transient thermal system has been analyzed and the results have been compared with experimental results in order to decrease the armature weigh and increase efficiency. Also, in experimental studies thermal camera and thermocouples have been used for thermal measurements. Finally, multi-objective optimization has been performed to decrease the armature weight, while keeping maximum temperature on armature between in safely working interval.
Keywords: thermal analysis; CFD; LED armature; optimization; LIGHT EMISSION; CONSERVATION; EFFICIENT